2020
DOI: 10.4081/pr.2020.8702
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Breastfeeding Pillow to Reduce Discomfort for Breastfeeding Mothers

Abstract: The process of breastfeeding for newborns in the special care room often experiences obstacles due to diverse factors, such as environmental factors, hospitalization impact, and maternal discomfort during breastfeeding. The aim of this study was to determine whether breastfeeding pillows decrease maternal discomfort during breastfeeding. This research employed a randomized control trial (RCT) design involving 70 participants who were divided into an intervention (n=35) and a control group (n=35) based on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Researchers conducted a study about the breastfeeding experiences of mothers with physical disabilities in the United States, and reported that the presence of assistive equipment (nursing pillows and breast pumps) enabled some to breastfeed; however, many participants could not effectively utilize these resources independently and breastfeeding ended prematurely (Powell et al, 2018). The effective use of breastfeeding aids increases comfort for the mother during the breastfeeding process and ensures the continuity of breastfeeding (Sri Widiastuti et al, 2020). Considering the positive influences of these assistive devices, it is extremely important that mothers with disabilities have easy access to them and that any adaptations to their design and use target individualized areas of need.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers conducted a study about the breastfeeding experiences of mothers with physical disabilities in the United States, and reported that the presence of assistive equipment (nursing pillows and breast pumps) enabled some to breastfeed; however, many participants could not effectively utilize these resources independently and breastfeeding ended prematurely (Powell et al, 2018). The effective use of breastfeeding aids increases comfort for the mother during the breastfeeding process and ensures the continuity of breastfeeding (Sri Widiastuti et al, 2020). Considering the positive influences of these assistive devices, it is extremely important that mothers with disabilities have easy access to them and that any adaptations to their design and use target individualized areas of need.…”
Section: Discussionmentioning
confidence: 99%
“…However, strenuous exercises that can jeopardize the lives of the mother and the foetus such as a long jump should be avoided. In addition, if pregnant women developed reduced HGS that extended to after delivery, measures such as the use of adaptation pillow can be used to offer some support during breasting or holding the baby [42]. Upper limb functional activities such as opening jars and carrying bags during pregnancy could also help influence HGS.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding pillows or cushions can provide extra support for the mother and baby, helping maintain a comfortable position during feeding. Seeking help from a lactation consultant or attending breastfeeding support groups can also provide valuable guidance on proper latch technique and positioning, ensuring effective breastfeeding [ 73 ].…”
Section: Reviewmentioning
confidence: 99%